Risk Factors for Human Papillomavirus Infection and Abnormal Cervical Cytology Among Perinatally Human Immunodeficiency Virus-Infected and Uninfected Asian Youth. (30th March 2018) - Sohn, Annette H; Kerr, Stephen J; Hansudewechakul, Rawiwan; Gatechompol, Sivaporn; Chokephaibulkit, Kulkanya; Dang, Hanh Le Dung; Tran, Dan Ngoc Hanh; Achalapong, Jullapong; Teeratakulpisarn, Nipat; Chalermchockcharoenkit, Amphan; Thamkhantho, Manopchai; Pankam, Tippawan; et al.
Abstract : In an observational study of perinatally human immunodeficiency virus (HIV)–infected (PHIV) adolescents matched by age and sexual activity to uninfected females in Thailand and Vietnam, PHIV adolescents had higher rates of anogenital infection with high-risk human papillomavirus and abnormal cervical Pap smears. Abstract: Background: Infection with high-risk human papillomavirus (HR-HPV) may be higher in perinatally human immunodeficiency virus (HIV)–infected (PHIV) than HIV-uninfected (HU) adolescents because of long-standing immune deficiency. Methods: PHIV and HU females aged 12–24 years in Thailand and Vietnam were matched by age group and lifetime sexual partners. At enrollment, blood, cervical, vaginal, anal, and oral samples were obtained for HPV-related testing. The Wilcoxon and Fisher exact tests were used for univariate and logistic regression for multivariate analyses. Results: Ninety-three PHIV and 99 HU adolescents (median age 19 [18–20] years) were enrolled (June 2013–July 2015). Among PHIV, 94% were currently receiving antiretroviral therapy, median CD4 count was 593 (392–808) cells/mm 3, and 62% had a viral load <40 copies/mL. Across anogenital compartments, PHIV had higher rates of any HPV detected (80% vs 60%; P = .003) and any HR-HPV (60% vs 43%, P = .02). Higher proportions of PHIV had abnormal Pap smears (eg, atypical squamous cells of unknown significance [ASC-US], 12% vs 14%; low-grade squamous intraepithelial neoplastic lesions, 19% vs 1%). After adjusting for ever being pregnant and asymptomatic sexually transmitted infections (STI) at enrollment, PHIV were more likely to have HR-HPV than HU (odds ratio, 2.02; 95% confidence interval, 1.09–3.77; P = .03). Conclusions: Perinatal HIV infection was associated with a higher risk of HR-HPV and abnormal cervical cytology. Our results underscore the need for HPV vaccination for PHIV adolescents and for prevention and screening programs for HPV and other STIs.